M-substituted (M = Co, Ni and Cu) zinc ferrite photo-catalysts for hydrogen production by water photo-reduction. (13th July 2016) - Boudjemaa, Amel; Popescu, Ionel; Juzsakova, Tatjana; Kebir, Mohammed; Helaili, Nassima; Bachari, Khaldoun; Marcu, Ioan-Cezar
Abstract: A0.2 Zn0.8 Fe2 O4 ferrites with A = Co, Ni and Cu were successfully prepared by co-precipitation followed by annealing at 650 °C. They were characterized by using XRD, EDX, BET, FTIR, RDS, electrical conductivity, Current-Potential, Mott–Schottky and Nyquist techniques and their photo-catalytic properties were evaluated in hydrogen production through water photo-reduction. XRD revealed the formation of cubic ferrospinel structures with particle sizes in the nano-range. BET surface areas of the ternary spinels were higher than that of the binary ZnFe2 O4 . The electrical conductivities of A0.2 Zn0.8 Fe2 O4 were found to obey the Arrhenius law with activation energies of conduction between 0.17 and 0.31 eV. They were found to be n-type semiconductors with narrow band gap. The photo-catalytic results for hydrogen production indicated that the Co substitution dramatically enhances the catalytic activity of ZnFe2 O4 . This substituted zinc ferrite shows the highest photo-catalytic activity under visible light irradiation, which varies as follows: Co0.2 Zn0.8 Fe2 O4  >> Ni0.2 Zn0.8 Fe2 O4  > ZnFe2 O4  > Cu0.2 Zn0.8 Fe2 O4 . Highlights: A0.2 Zn0.8 Fe2 O4 was synthesized by co-precipitation method. A0.2 Zn0.8 Fe2 O4 was used as heterogeneous photo-catalyst for hydrogen production. Co0.2 Zn0.8 Fe2 O4 was highly efficient to produce hydrogen under visible light irradiation.